2020
DOI: 10.3390/antiox9111029
|View full text |Cite
|
Sign up to set email alerts
|

Seizure-Induced Oxidative Stress in Status Epilepticus: Is Antioxidant Beneficial?

Abstract: Epilepsy is a common neurological disorder which affects patients physically and mentally and causes a real burden for the patient, family and society both medically and economically. Currently, more than one-third of epilepsy patients are still under unsatisfied control, even with new anticonvulsants. Other measures may be added to those with drug-resistant epilepsy. Excessive neuronal synchronization is the hallmark of epileptic activity and prolonged epileptic discharges such as in status epilepticus can le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
45
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(48 citation statements)
references
References 187 publications
(225 reference statements)
2
45
0
1
Order By: Relevance
“…Evidence has demonstrated that oxidative stress plays pivotal role in the pathophysiology of seizures. Researches have determined that antioxidants exerted anticonvulsant effects [17][18][19]. In line with aforementioned studies, our findings showed that Artemisia persica extract reduced the MDA levels and increased total antioxidant capacity in the serum and prefrontal cortex samples in PTZ-induced mice.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Evidence has demonstrated that oxidative stress plays pivotal role in the pathophysiology of seizures. Researches have determined that antioxidants exerted anticonvulsant effects [17][18][19]. In line with aforementioned studies, our findings showed that Artemisia persica extract reduced the MDA levels and increased total antioxidant capacity in the serum and prefrontal cortex samples in PTZ-induced mice.…”
Section: Discussionsupporting
confidence: 90%
“…Ample evidence demonstrated that mitochondrial dysfunction and oxidative stress play pivotal role in the pathophysiology of seizures. In this concept, research studies determined that antioxidants exerted anticonvulsant properties [17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, since various cell models of epilepsy show a deficiency in coenzyme Q 10 (CoQ), supplementation of CoQ has been used as a treatment to alleviate pathophysiological disruptions. Importantly, CoQ supplementation has been shown to result in the enhancement of mitophagy flux via activation of AMPK, which in turn activates Silent Mating Type Information Regulation 2, S. Cerevisiae, Homolog 1 (SIRT1) and PGC-1α, leading to the induction of a metabolic stress resistance program that includes the induction of autophagy [ 205 ].…”
Section: Mitophagy In Neuropsychiatric and Neurodegenerative Diseasesmentioning
confidence: 99%
“…Iron is also abundant in the brain and is involved in the formation of hydroxyl radicals (Valko et al, 2007). Therefore, overproduction of oxidative stress in the brain leads to lipid peroxidation, epileptic activity, and neuronal death (Lin et al, 2020). Due to the essential role of oxidative stress and lipid peroxidation in inducing ferroptosis, these epileptic pathological processes in the brain are closely related to ferroptosis.…”
Section: Links Between Ferroptosis and Epilepsymentioning
confidence: 99%